Pengaruh Pengetahuan, Ketegasan Sanksi dan Sistem Administrasi Perpajakan dalam Membayar PBB DI Kecamatan Juhar - Tan Kim Hek; Andriasan Sudarso (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2023)
This study is to examine the influence of tax knowledge, firmness of tax sanctions, and tax amnesty against about obedience to taxpayer. This study focus on taxpayers every people who were in district of Juhar to know: (1) Influence of knowledge about obedience taxpayer, (2) Influence of assertiveness tax sanctions to taxpayer, and (3) Influence of tax administration system taxpayers. Used data is the primary data from the spread of the questionnaire to 97 respondents and data that can be processed as much as 30 questionnaires. Method of sample collection is use convenience sampling. Technique used data analysis is the technique of regressing linear doubled. Regression test results showed that (1) knowledge of tax that influence of positive and significant about obedience taxpayers, (2) assertiveness tax sanctions that influence of positive and significant about obedience taxpayers, and (3) tax administration system influential positive and significant about obedience taxpayers. The magnitude of the influence variable independent seen from the value of the coefficient determination (R2) of 0,553, which means that the knowledge of tax, assertiveness sanctions taxes, and tax administration system give the influence of positive towards of docility taxpayers of 55,3%.Â Â